Isles of Noise : Sonic Media in the Caribbean - Bronfman, Alejandra, 1962- (Book collections on Project MUSE., 2016)
In this media history of the Caribbean, Alejandra Bronfman traces how technology, culture, and politics developed in a region that was 'wired' earlier and more widely than many other parts of the Americas. Attending to everyday life, infrastructure, and sounded histories, Bronfman does not allow the notion of empire to stand solely for domination.